P057 Virus aerosol propagation by CPAP is proportional to mask leak and can be prevented by use of a hood and air filtration system. (7th October 2021) - Landry, S; Barr, J; MacDonald, M; Hamilton, G; Mansfield, D; Edwards, B; Joosten, S
Abstract: Introduction: Nosocomial transmission of SARS-CoV-2 has caused significant morbidity/mortality in the COVID-19 pandemic. Because patients auto-emit aerosols containing viable virus, these aerosols can be further propagated when patients undergo certain treatments including continuous positive airway pressure (PAP) therapy. This study aimed to assess the degree of viable virus propagated from mask leak in a PAP circuit. Methods: Bacteriophage PhiX174 (108copies/mL) was nebulised into a custom PAP circuit. Mask leak was systematically varied to 0, 7, 21, 28 and 42 L/min at the mask interface. Plates containing Escherichia coli assessed the degree of viable virus settling on surfaces around the room. In order to contain virus spread a ventilated headboard and high efficiency particulate air (HEPA) filter was tested. Results: Increasing mask leak was associated with virus contamination in a dose response manner (χ2= 58.24, df=4, p<0.001). Clinically relevant levels of leak (≥21 L/min) were associated with virus counts equivalent to using PAP with a standard vented mask. Viable viruses were recorded on all plates (up to 3.86m from source). A plastic hood with HEPA filtration significantly reduced viable viruses on all plates. HEPA exchange rates of 170 and 470m3/hr eradicated all evidence of virus contamination. Discussion: Mask leak from PAP circuits may be a major source of environmental contamination and nosocomial spread of infectious respiratory diseases. Subclinical levels of leak should be treated as an infectious risk. Cheap and low-cost patient hoods with HEPA filtration are an effective countermeasure.